Uma aplicação da teoria de Ramsey ao teorema de Schur - Araujo, Liliane Teixeira Pina (2019)
In this dissertation, we will make a brief introduction to Ramsey’s theory. As an application of the results presented we will demonstrate the theorem of a version of the celebrated Fermat’s Last Theorem in the context of residual bodies Zp.